Consumer Behavior, Organizational Strategy and Financial Economics Proceedings of the 21st Eurasia Business and Economics Society Conference (Eurasian Studies in Business and Economics,, 2018)
This volume presents selected articles from the 21st Eurasia Business and Economics Society (EBES) Conference, which was held in Budapest (Hungary) in 2017. The theoretical and empirical papers in this volume cover various areas of business, economics, and finance from a diverse range of regions. In particular, this volume focuses on the latest trends in consumer behavior, new questions in the development of organizational strategy, and the interaction of financial economics with industrial economics and policy.